E-Learning in Islamic Religious Education: Improving Access and Quality of Learning - Thoyyibah, Hayatun; Murthasiah, Dewi; Kholilah, Aulia; Nubzatussaniyyah, Nunu (Zona Education Indonesia, 2024)
This study explores the impact of e-learning on Islamic Religious Education (IRE) in secondary schools across Indonesia, focusing on both its benefits and challenges. The research involved 100 teachers and 500 students, examining their experiences with e-learning. Results indicate that e-learning has significantly enhanced students' understanding of IRE materials, with 75% of students and 80% of teachers reporting improved engagement and motivation. However, challenges such as limited technology access, particularly in rural areas, and resistance to traditional teaching methods persist. The study highlights the importance of comprehensive digital training for teachers, improved technological infrastructure, and the active involvement of parents and school management in supporting e-learning. Findings suggest that effective implementation of e-learning can greatly advance the quality and accessibility of IRE, helping to foster a generation that is both intellectually competent and ethically grounded according to Islamic teachings. Recommendations include collaborative efforts to enhance technology access, continuous teacher training, and development of interactive e-learning modules to address the identified challenges